O processo de institucionalização de idosos em Porto Alegre-RS - Malheiro, Alessandra Domingues (2012)
This study concerns the theme of elderly institutionalization. The current paper aims to verify what the process of elderly institutionalization at nursing homes in Porto Alegre- RS is like, verify elderly decision and choice concerning their institutionalization process, identify elderly participation and (not) acceptance concerning the situation of living at long-term institutions addressed to elderly (ILPIs) and verify the familiar relationships involved in such processes. To do so, 25 semi-structured interviews with elderly and nursing homes staff members were conducted between October 2010 and December 2011. The study shows that most of ILPIs residents were women, none of the interviewers were accompanied by their spouse at the moment of the interview and most of them had children. Most of the interviewees have stated that both the idea of moving in to a nursing home and the choice for such nursing home had been made by their family members. Among other reasons to sheltering risen by both elderly and ILPI staff members are: the demand for a place capable of providing better cares and/or health treatments, problem with caretakers and/or accompanying at home and search for a place where the elderly would not feel lonely. Most of elderly interviewed thinks that being at a nursing home is a good thing and this fact could be related to the kinds of cares devoted to elderly in such places as well as to the nursing home s physical space and also to the playful and leisure activities developed at such homes. All the elderly interviewed reported being visited by their family members.